Synergistic interaction of big data with cloud computing for Industry 4.0 - Zalte, Sheetal S.; Chatterjee, Indranath; Kamat, Rajanish K. (Boca Raton : CRC Press, 2023)
"Synergistic Interaction of Big Data with Cloud Computing for Industry 4.0 discusses how to develop adaptive, robust, scalable, and reliable applications used in solutions for day-to-day problems. It reviews the advantages and consequences of utilizing Cloud Computing to tackle Big Data issues within the manufacturing and production sector as part of Industry 4.0. Top Big Data experts throughout the world have contributed their expertise to this book, addressing the major challenges, issues, and advances in Big Data and Cloud Computing for Industry 4.0"--
Bigdata based on fuzzy time series forecasting for stock index prediction / Ruchismita Majumder, Partha Pratim Deb, Diptendu Bhattacharya -- Big data based time series forecasting using FB prophet for stock index / Debankita Mukhopadhyay, Sourabarna Roy, Partha Pratim Deb -- The impact of artificial intelligence and big data in the postal sector / Mary Olawuyi Ojo, Indranath Chatterjee, Sheetal Gaikwad -- Advances in cloud technologies and future trends / Indra Kumari, Jungsuk Song, Buseung Cho -- Reinforcement of the multi-cloud infrastructure with edge computing / L. Steffina Morin, P. Murali -- Study and investigation of PKI based blockchain infrastructure / R. Deshmukh, S. Gaikwad -- Stock index forecasting using stacked LTSM -- deep learning & big data / Debasmita Pal, Partha Pratim Deb -- A comparative study and analysis of time-series and deep learning algorithms for bitcoin price prediction / Sagar Chakraborty, Nivedita Das, Kisor Ray -- Machine learning for healthcare / Udeechee, T.V. Vijay Kumar -- Transfer learning and fine tuning based early detection of cotton plant disease / Himani Bhatheja, N. Jayanthi -- Recognition of facial expressions of infrared images for lie detection with the use of support vector machine / Rupali Dhabarde, D.V. Kodavade, Rashmi Deshmukh, Sheetal Gaikwad -- SVM for classification of remote sensing images -- a review / Parijata Majumdar, Suchanda Dey, Sourav Bardhan, Sanjoy Mitra -- A study on data cleaning of hydrocarbon resource under deep sea water using imputation technique based approach of data science / Dipjyoti Deb.
OCLC-licensed vendor bibliographic record.
Keywords: Big data; Cloud computing; Industry 4.0.; TECHNOLOGY / Manufacturing; COMPUTERS / Database Management / Data Mining